#### Answer

Correct

#### Work Step by Step

$9+7x+(-2)=7x+9+(-2)\rightarrow$ apply commutative property
$7x+9+(-2)=7x+9+(-2)$

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

Correct

$9+7x+(-2)=7x+9+(-2)\rightarrow$ apply commutative property
$7x+9+(-2)=7x+9+(-2)$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.